PELAKSANAAN PAGANG GADAI SAWAH BERDASARKAN HUKUM ADAT DI KANAGARIAN KOTO TINGGI KECAMATAN BASO KABUPATEN AGAM PROVINSI SUMATERA BARAT - Farhan Muhammad Aziz; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Land is an important element of the formation of the State, in achieving the goals of the State, government intervention is needed, but the cultural diversity of each region is one of the obstacles to the implementation of national law, pawning land is one of the land transactions that still exists and is the needs of Indonesian indigenous peoples including customary law Minangkabau. Where transactions are carried out by Minangkabau indigenous people especially in Kanagarian Koto Tinggi, Agam Regency where many transactions have taken place for decades without any time limit, either orally or in writing.The purpose of this research is to find out how the implementation of the existing pawn apprenticeships in Koto Tinggi Kanagarian and what are the legal consequences of the implementation of the pawn apprenticeship. This type of research is sociological juridical, analytic descriptive research. The research location was Kanagarian Koto Tinggi, Baso Subdistrict, Agam Regency, West Sumatra Province. Data sources used, primary data, secondary data and tertiary data. Data collection techniques with interviews and literature review.From the results of this study, it was concluded that, first, the pawning process in Koto Tinggi Kanagarian began with the agreement of families and people who would pawn the fields and the implementation did not use a time limit. Second, it has been going on for decades ago redemption is based on the price of gold at the time of redemption so that debtors are unable to cut down especially the middle to lower class because the price of gold has gradually increased in price. The author's suggestion is, first, the Government of Agam Regency, West Sumatra Province in general, make a written rule regarding the implementation of pawning apprenticeships, so that with this regulation facilitate the implementation of pawning apprenticeships by the Minangkabau community and mutual benefit between the parties. Second, the Government must be able to socialize, so that the purpose of Article 7 of Law No. 56 of 1960 concerning the Determination of Agricultural Land Area can be achieved.Keywords: Pawn Merchants - Customary Law - In Minangkabau